Hormesis and Female Sex Hormones - Strom, Jakob O. (MDPI, 2011)
Hormone replacement after menopause has in recent years been the subject of intense scientific debate and public interest and has sparked intense research efforts into the biological effects of estrogens and progestagens. However, there are reasons to believe that the doses used and plasma concentrations produced in a large number of studies casts doubt on important aspects of their validity. The concept of hormesis states that a substance can have diametrically different effects depending on the concentration. Even though estrogens and progestagens have proven prone to this kind of dose-response relation in a multitude of studies, the phenomenon remains clearly underappreciated as exemplified by the fact that it is common practice to only use one hormone dose in animal experiments. If care is not taken to adjust the concentrations of estrogens and progestagens to relevant biological conditions, the significance of the results may be questionable. Our aim is to review examples of female sexual steroids demonstrating bidirectional dose-response relations and to discuss this in the perspective of hormesis. Some examples are highlighted in detail, including the effects on cerebral ischemia, inflammation, cardiovascular diseases and anxiety. Hopefully, better understanding of the hormesis phenomenon may result in improved future designs of studies of female sexual steroids.